2020
DOI: 10.1016/j.heliyon.2020.e05803
|View full text |Cite
|
Sign up to set email alerts
|

Dietary risk assessment of organochlorine pesticide residues in maize-based complementary breakfast food products in Nigeria

Abstract: The study assessed the levels of organochlorine pesticides (OCPs) in eight brands (A-H) of regularly consumed maize-based complementary/breakfast foods in Nigeria. We also evaluated the dietary exposure of infants and young children to the detected OCPs. The OCP residues were quantified using GC-ECD. A total of 10 OCPs residues (β-HCH, δ- HCH, heptachlor, endosulfan sulfate, aldrin, endrin, dieldrin, p,p’ -DDE, p,p’ -DDT and methoxychlor) were detected. Total OCPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Hence, they have been widely reported in food crops [1-9, 55, 72]. Some OCPs in this study such as β-HCH, Heptachlor, Endosulfan, Aldrin, Lindane, Dieldrin, p,p'-DDE, p,p'-DDT have been previously reported in maize, beans, millet and rice in Nigeria [85][86][87][88]. Similarly, Akinneye et al [89] reported Dichlorvos, Carbofuran, Carbaryl, Diazinon, Pirimiphos-methyl, Malathion, Chlorpyrifos as the OPPs and carbamates in beans, rice, wheat and maize samples collected from Ondo State.…”
Section: Determine the Concentration Of Identified Pesticides In Grainsmentioning
confidence: 72%
“…Hence, they have been widely reported in food crops [1-9, 55, 72]. Some OCPs in this study such as β-HCH, Heptachlor, Endosulfan, Aldrin, Lindane, Dieldrin, p,p'-DDE, p,p'-DDT have been previously reported in maize, beans, millet and rice in Nigeria [85][86][87][88]. Similarly, Akinneye et al [89] reported Dichlorvos, Carbofuran, Carbaryl, Diazinon, Pirimiphos-methyl, Malathion, Chlorpyrifos as the OPPs and carbamates in beans, rice, wheat and maize samples collected from Ondo State.…”
Section: Determine the Concentration Of Identified Pesticides In Grainsmentioning
confidence: 72%
“…Heptachlor should have been phased-out of agrochemical stores among the insecticides that have been banned in Nigeria. However, it is alleged that it is either marketed under various names or labels or added to other pesticides currently in use by Nigerian farmers as one of the active ingredients ( Sosan et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pesticides include dangerous agents such as organochlorine pesticides, as well as less harmful substances. Organochlorine compounds are characterized by a high ability to accumulate and a long half-life, which makes them very toxic to the human body [ 107 ]. The sources of human exposure to pesticides are meat, fish, dairy products, and drinking water.…”
Section: Discussionmentioning
confidence: 99%